2015
DOI: 10.20344/amp.5775
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis to the Glans Penis: An Unusual Site of Rectal Cancer Recurrence

Abstract: RESUMOA doença secundária do pénis é uma situação clínica frequentemente associada a doença disseminada e as localizações mais comuns são os órgãos genito-urinários. O prognóstico é mau e as opções de tratamento incluem: penectomia; excisão local; radioterapia; quimioterapia; terapêutica de suporte. Apesar das várias terapêuticas existentes, nenhuma na literatura é apontada como superior às restantes. Os autores documentam o caso de um doente de 66 anos com metástase da glande peniana em contexto de adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Local symptom control was achieved by administering 35Gy in 14 fractions using the 3D conformal technique [ 12 ] to the penis in one case and 40Gy in the other report (fractionation and technique were not described) [ 13 ]. Similarly, it has been reported that complete relief pain and priapism can be achieved by locally administering 30Gy in 10 fractions in metastatic bladder urothelial carcinoma [ 21 ] and metastatic rectal adenocarcinoma [ 32 ] using the 3D conformal technique. On the contrary, priapism symptoms were only partially relieved in earlier case reports [ 20 , 28 ], even with a higher dose (56Gy) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local symptom control was achieved by administering 35Gy in 14 fractions using the 3D conformal technique [ 12 ] to the penis in one case and 40Gy in the other report (fractionation and technique were not described) [ 13 ]. Similarly, it has been reported that complete relief pain and priapism can be achieved by locally administering 30Gy in 10 fractions in metastatic bladder urothelial carcinoma [ 21 ] and metastatic rectal adenocarcinoma [ 32 ] using the 3D conformal technique. On the contrary, priapism symptoms were only partially relieved in earlier case reports [ 20 , 28 ], even with a higher dose (56Gy) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a 3DCRT treatment for a total dose of 30 Gy in 10 fractions was used in association with capecitabine in a penile localization from rectal cancer, with a complete response consisting in a resolution of the penile lesion [10]. In another experience from 2015, a radiotherapy course of 30 Gy in 10 fractions was delivered with adjuvant intent after circumcision and modified glansectomy to prevent local recurrence in rectal adenocarcinoma histology proven metastasis: despite patient poor outcome because of overall burden of disease, six months after palliative treatment no local recurrence was noted [11]. Masbridge et al reported the early detection of a case of penile metastasis from prostate cancer thanks to the use of PSMA-PET/CT [12].…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, important to be aware that, although the appearance of penile cancer is clear in the majority of cases, there are some rare alternative presentations. Penile metastasis has been reported from sites such as bladder (Valsero et al, 2013), prostate (Sánchez et al, 2011) and rectum (Nunes et al, 2015). Additionally, inflammatory lesions can occasionally mimic the appearance of a penile cancer (Alnajjar et al, 2016).…”
Section: The Role Of Penile Biopsymentioning
confidence: 99%